Adoption of electric vehicles in corporate enterprises: enhancing sustainability, economic efficiency, and operational management - Orhan Topal (CT&F Ciencia, Tecnología & Futuro)
The global automotive industry is currently undergoing a transformation driven by a number of factors, including environmental concerns, sustainability targets, and the advent of innovative technologies. The adoption of electric vehicles represents a pivotal aspect of this transformation, offering individual and corporate users in the car rental sector a significant alternative to traditional internal combustion engine vehicles. The economic and operational advantages of electric vehicles, coupled with the opportunity for car rental companies to fulfil their environmental responsibilities, are accelerating the transformation of the automotive industry.